Pathological classification of human iPSC-derived neural stem/progenitor cells towards safety assessment of transplantation therapy for CNS diseases. Issue 1 (December 2016) - Sugai, Keiko; Fukuzawa, Ryuji; Shofuda, Tomoko; Fukusumi, Hayato; Kawabata, Soya; Nishiyama, Yuichiro; Higuchi, Yuichiro; Kawai, Kenji; Isoda, Miho; Kanematsu, Daisuke; Hashimoto-Tamaoki, Tomoko; Kohyama, Jun; et al.
Abstract The risk of tumorigenicity is a hurdle for regenerative medicine using induced pluripotent stem cells (iPSCs). Although teratoma formation is readily distinguishable, the malignant transformation of iPSC derivatives has not been clearly defined due to insufficient analysis of histology and phenotype. In the present study, we evaluated the histology of neural stem/progenitor cells (NSPCs) generated from integration-free human peripheral blood mononuclear cell (PBMC)-derived iPSCs (iPSC-NSPCs) following transplantation into central nervous system (CNS) of immunodeficient mice. We found that transplanted iPSC-NSPCs produced differentiation patterns resembling those in embryonic CNS development, and that the microenvironment of the final site of migration affected their maturational stage. Genomic instability of iPSCs correlated with increased proliferation of transplants, although no carcinogenesis was evident. The histological classifications presented here may provide cues for addressing potential safety issues confronting regenerative medicine involving iPSCs.